2002
DOI: 10.1097/00000658-200210000-00003
|View full text |Cite
|
Sign up to set email alerts
|

A New TNM Staging Strategy for Node-Positive (Stage III) Colon Cancer

Abstract: The current stage III designation of colon cancer excludes prognostic subgroups stratified for mural penetration (T1-4) or nodal involvement (N1 vs. N2). Analysis of a large data set supports stratification into three subsets, confirming the benefit of adjuvant chemotherapy in each subgroup. This strategy should be used in the reporting and staging of node-positive colon cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
131
0
10

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 216 publications
(143 citation statements)
references
References 16 publications
2
131
0
10
Order By: Relevance
“…Although histological grading plays a significant role in disease prognosis (Greene et al, 2002), it is not part of the TNM classification (Compton et al, 2002). Our study also demonstrates a high correlation between tumor grading and recurrence (p<0.008).…”
Section: Discussionmentioning
confidence: 55%
“…Although histological grading plays a significant role in disease prognosis (Greene et al, 2002), it is not part of the TNM classification (Compton et al, 2002). Our study also demonstrates a high correlation between tumor grading and recurrence (p<0.008).…”
Section: Discussionmentioning
confidence: 55%
“…Scheithauer et al 182 Cochrane Database 183 Saltz et al 120 and de Gramont et al 131 Goldberg et al 135 and Fuchs et al 121 Hurwitz et al 146 Tumor invades submucosa T 2 Tumor invades muscularis propia T 3 Tumor invades through the muscularis propria into the subserosa T 4 Tumor directly invades other organs or structures, or perforates visceral Peritoneum Regional lymph nodes (N) N x…”
Section: Adapted With Permission From Meyerhardt and Mayer 31mentioning
confidence: 99%
“…When patients have a similar number of lymph node resections, a higher number of lymph nodes involved is associated with inferior survival and worse outcomes [4,5]. Furthermore, Aldecoa et al showed that higher molecular lymph node tumor burden in grossly negative lymph node cancer (Stage I–II) is associated with inferior prognosis [6].…”
Section: Introductionmentioning
confidence: 99%